Policy statement from the Society for Healthcare Epidemiology of America (SHEA): Only medical contraindications should be accepted as a reason for not receiving all routine immunizations as recommended by the Centers for Disease Control and Prevention. (17th January 2021) - Weber, David J.; Talbot, Thomas R.; Weinmann, Allison; Mathew, Trini; Heil, Emily; Stenehjem, Edward; Duncan, Robert; Gross, Alan; Stinchfield, Patricia; Baliga, Christopher; Wagner, Jamie; Schaffner, William; et al.
Summary: SHEA endorses adhering to the recommendations by the CDC and ACIP for immunizations of all children and adults. All persons providing clinical care should be familiar with these recommendations and should routinely assess immunization compliance of their patients and strongly recommend all routine immunizations to patients. All healthcare personnel (HCP) should be immunized against vaccine-preventable diseases as recommended by the CDC/ACIP (unless immunity is demonstrated by another recommended method). SHEA endorses the policy that immunization should be a condition of employment or functioning (students, contract workers, volunteers, etc) at a healthcare facility. Only recognized medical contraindications should be accepted for not receiving recommended immunizations.